2021
DOI: 10.1111/jocd.14088
|View full text |Cite
|
Sign up to set email alerts
|

Fractional carbon dioxide laser versus trichloroacetic acid peel in the treatment of pseudo‐acanthosis nigricans

Abstract: Acanthosis nigricans is a common pigmentary disorder characterized by hyperpigmented and hyperkeratotic velvety skin lesions that presents mainly on the flexural sites, for example, the neck, the axillae, and groin. 1 The pathogenesis is mostly attributed to increased insulin resistance and hyperinsulinemia that result in stimulation of insulin growth factor 1 (IGF-1) receptors on keratinocytes and fibroblasts, leading to cellular proliferation. The dark color of AN is mostly due to hyperkeratosis rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
6
0
3
Order By: Relevance
“…There was overall improvement in area index, severity and texture across time subjected to CO2 laser (p < 0.001). This finding is in agreement with Eldeeb et al (13) study who reported that the use of fractional CO2 laser resulted in marked improvement of both the texture and pigmentation of AN. In contrast to the current findings, Zaki et al (9) study demonstrated that the mean severity of the lesion did not improve after using CO2 laser on the right side of the neck, where the mean Acanthosis Nigricans Area and Severity Index (ANASI) at the start of the study was 23.50 ± 8.85, and after the laser treatment sessions, it became 19.10 ± 7.62, (P value = 0.1) which showed no statistical improvement.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There was overall improvement in area index, severity and texture across time subjected to CO2 laser (p < 0.001). This finding is in agreement with Eldeeb et al (13) study who reported that the use of fractional CO2 laser resulted in marked improvement of both the texture and pigmentation of AN. In contrast to the current findings, Zaki et al (9) study demonstrated that the mean severity of the lesion did not improve after using CO2 laser on the right side of the neck, where the mean Acanthosis Nigricans Area and Severity Index (ANASI) at the start of the study was 23.50 ± 8.85, and after the laser treatment sessions, it became 19.10 ± 7.62, (P value = 0.1) which showed no statistical improvement.…”
Section: Discussionsupporting
confidence: 93%
“…All cases were females and mean age was 17.5 ranging from 6 to 39 years. Female preponderance was reported by Zaki et al (9) , Eldeeb et al (13) and Leerapongnan et al (12) studies. Conversely, Thomas et al (14) study has shown that AN is more prevalent in the male population [55 were male (55%) and the rest 45 were female (45%)].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The aim of treatment in AN is to treat the associated disorder and treatment of the pigmentation lesion. 16 There was a significant improvement in ANASI score and MI index in our study after fractional CO 2 laser; this can be explained by the fact of making skin columns of thermal injury known as micro-thermal zones and removing thin layers of skin with minimal thermal damage leading to collagen injury and collagen remodeling. 10 In addition, transepidermal 712 elimination of the dermal content is the possible mechanism by which melanin is eliminated.…”
Section: Discussionmentioning
confidence: 48%
“…The aim of treatment in AN is to treat the associated disorder and treatment of the pigmentation lesion. 16 …”
Section: Discussionmentioning
confidence: 99%